ZBIRKA MAKEDONSKIH LJUDSKIH PRAVLJIC SONČEVA SESTRA V MEDKULTURNEM KONTEKSTU (Philological Studies, 2019)
The collection of twenty-two Macedonian folktales translated into Slovenian was student project in 2006 with profound title Sun’s sister. The collection includes the following tales (in alphabetical order) About sons and money, Good for good, Loggers who knows the language of animals, Mara the Cinderella, Shepherd and three fairies, Sun’s sister, The Apple and two wife, The lost tsarina, The mole is priest’s son, Three father commandments to son and Wolf, Three sisters, Three weavers, Tower of human heads, Tri fairies and child, Tsar and three sons, Tsar with three sons and three apples, Tsars daughter and drum, Tsars daughter that would not like to marriage, Ungrateful Snake to shepherd and ungrateful shepherd to fox, Wisdom and happiness, Young man who wanted to learn woman cunning,
Keywords: Sun’s sister, ATU 311, Hans Jorg er, Max Lüthi, Jack Zipes, intercultural